Starting the data conversation: informing data services at an academic health sciences library. - Read, Kevin B.; Surkis, Alisa; Larson, Catherine; McCrillis, Aileen; Graff, Alice; Nicholson, Joey; Juanchan Xu (Journal of the Medical Library Association, 2015)
Objective: The research obtained information to plan data-related products and services. Methods: Biomedical researchers in an academic medical center were selected using purposive sampling and interviewed using open-ended questions based on a literature review. Interviews were conducted until saturation was achieved. Results: Interview responses informed library planners about researchers' key data issues. Conclusions: This approach proved valuable for planning data management products and services and raising library visibility among clients in the research data realm.